Another day - Levithan, David (2015)
"Rhiannon is disappointed that her neglectful boyfriend Justin doesn't remember the one perfect day they shared, until a stranger tells her that the Justin she spent that day with, the one who made her feel like a real person... wasn't Justin at all"--
Companion book to: Every day.
Keywords: High schools -- Fiction; Schools -- Fiction; Identity (Philosophical concept) -- Fiction; Young adult fiction